A Translation-Oriented Approach to Person Deixis - Oana-Maria PUIU (Scientific Bulletin of the Politehnica University of Timişoara: Transactions on Modern Languages, 2021)
The paper focuses on the equivalence of person deixis in the translation of the World Health Organization (WHO) institutional discourse in the context of COVID 19. Accordingly, the aim of the paper is twofold: to detect the linguistic and cultural gaps between the source text in English and the target text in Romanian with respect to the conceptualization and grammatical encoding of person deixis, and to determine the optimal, context-sensitive equivalents in translation. Our assumption is that, given the text type and the supranational identity of the text producer (WHO), the optimal equivalents will be based on cultural symmetry.